2015
DOI: 10.1177/0148607115585353
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin Preserves Goblet Cell Resistin‐Like Molecule β During Parenteral Nutrition but Not Other Goblet Cell Products

Abstract: Introduction Parenteral nutrition (PN) increases the risk of infection in critically ill patients and is associated with defects in gastrointestinal innate immunity. Goblet cells produce mucosal defense compounds including mucin (principally MUC2), trefoil factor 3 (TFF3,) and resistin-like molecule β (RELMβ). Bombesin (BBS), a gastin-releasing peptide analogue, experimentally reverses PN-induced defects in Paneth cell innate immunity. We hypothesized that PN reduces goblet cell product expression and PN+BBS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…All of these factors prevent bacteria from coming into contact with the subepithelial layer and thus inducing the inflammatory response. PN administration disturbs these systems [ 6 , 7 , 10 , 30 33 ], resulting in the increased exposure of antigens to the immune system, increased intestinal permeability, and the establishment of proinflammatory status in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors prevent bacteria from coming into contact with the subepithelial layer and thus inducing the inflammatory response. PN administration disturbs these systems [ 6 , 7 , 10 , 30 33 ], resulting in the increased exposure of antigens to the immune system, increased intestinal permeability, and the establishment of proinflammatory status in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors prevent bacteria from coming into contact with the sub-epithelial layer and thus inducing the inflammatory response. PN administration disturbs these systems (6, 7, 10, 30-33), resulting in the increased exposure of antigens to the immune system, increased intestinal permeability, and the establishment of pro-inflammatory status in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who have undergone an ileostomy, the number of goblet cells in the distal intestinal mucosa is significantly reduced relative to the proximal intestinal mucosa (25), and our studies also showed that the mucus layer of the distal intestinal mucosa is significantly thinner than that of the proximal intestinal mucosa (Figure 2). In mice with PN, although no changes were observed in total goblet cell numbers when compared with normal mice, levels of MUC2, RELMβ, and TFF3 in the ileum and luminal fluid were reduced (26). Similar to goblet cells, Paneth cells are specialized secretory epithelial cells resident in the small intestinal crypts of Lieberkühn (27).…”
Section: Changes In the Intestinal Mucosal Barriermentioning
confidence: 99%